1988
DOI: 10.1159/000242779
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Development of Porcine Fetal Adipose Tissue

Abstract: The influence of neural and endocrine status upon the metabolic activity and insulin responses of developing adipose tissue of fetal swine was examined. Central neural and endocrine regulation were removed by decapitation of fetuses at 45 days of gestation. Decapitated (decap) fetuses and intact littermates were removed at 65, 85 or 110 days of gestation. Fatty acid synthesis from glucose increased fivefold in slices of subcutaneous adipose tissue from intact fetuses and tenfold in tissue from decaps, between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In intact fetuses, the T4-associated increase in lipogenesis was suppressed by the addition of either isoproterenol + ADA or dbcAMP to the incubation medium. In hy poxed fetuses, the dramatic T4-associated in crease in lipogenesis was unaffected by incu bation with either isoproterenol or isoprotere nol + ADA but was somewhat suppressed by incubation with either forskolin (data not sh o w n ) or dbcAMP (table 3). Addition of in sulin (1 mU/ml) to the incubation medium induced a significant increase in lipogenesis in 90-day intact controls but had no effect on further stimulating lipogenesis in hypoxed and/or T4-treated fetuses (table 3).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…In intact fetuses, the T4-associated increase in lipogenesis was suppressed by the addition of either isoproterenol + ADA or dbcAMP to the incubation medium. In hy poxed fetuses, the dramatic T4-associated in crease in lipogenesis was unaffected by incu bation with either isoproterenol or isoprotere nol + ADA but was somewhat suppressed by incubation with either forskolin (data not sh o w n ) or dbcAMP (table 3). Addition of in sulin (1 mU/ml) to the incubation medium induced a significant increase in lipogenesis in 90-day intact controls but had no effect on further stimulating lipogenesis in hypoxed and/or T4-treated fetuses (table 3).…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies in our labo ratory demonstrated higher rates of de novo lipogenesis [4,5] and basal and insulin-stimu lated glucose metabolism [2,3] in adipose tis sue from fetal pigs in which central influences had been removed by fetal decapitation or hypophysectomy compared with tissue from control fetuses. In addition, the responsive ness of adipose tissue to (3-adrenergic stimula tion was abolished by fetal decapitation [1,2] or hypophysectomy [5] but unchanged by spi nal cauterization [2].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Central endocrine factor(s) arc believed es sential for the metabolic development of adi pose tissue [1][2][3][4]. Recent evidence suggests that thyroid hormones, which are under hypothalamic/pituitary control, play an important role in regulating such development [5][6][7], Previous studies in our laboratory demon strated that removal of central endocrine in fluences by hypophvsectomy of the fetal pig on day 70 of development induced fat cell hypertrophy [3] and elevations in lipoprotein lipase (LPL) activity [3], de novo lipogcnesis [4,5], and basal and insulin-stimulated glu cose metabolism [5] while decreasing fat cell number [6] and markedly impairing hor mone-stimulated lipolvsis [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The up‐regulation of PPARγ in hypoxed fetuses could explain some of the cellular results observed with this treatment. Hypophysectomy increases de novo lipogenesis, production of lipogenic enzymes such as lipoprotein lipase, and causes hypertrophy or an increase in fat cell size (29, 30, 31). Because PPARγ induces several adipogenic genes such as adipose fatty acid‐binding protein (aP2) and lipoprotein lipase, it is reasonable that an increase in PPARγ expression in hypoxed fetuses would account for the greater cell size and in‐creased lipogenesis.…”
Section: Discussionmentioning
confidence: 99%